2017
DOI: 10.3390/app7020187
|View full text |Cite
|
Sign up to set email alerts
|

Subcritical Water Extraction of Ursolic Acid from Hedyotis diffusa

Abstract: An efficient and environmental-friendly extraction method has been developed for extraction of ursolic acid (UA) from Hedyotis diffusa by using subcritical water extraction (SWE). The experiments were carried out at different particle sizes (20-100 mesh), extraction temperature (120-200 • C), extraction time (10-50 min), solvent/solid ratio (20-40 mL/g), and extraction pressure (0.6-3.0 MPa). Response surface methodology (RSM) was employed to optimize SWE conditions, and the maximum UA yield was 6.45 mg/g mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…It is also observed in the SWE of other natural product. 58,59 The effect of the solvent/solid ratio on the polysaccharide yield was explored from 15:1 to 55:1 (mL/g) with an extraction temperature of 140 °C, extraction time at 12.5 min, and extraction pressure at 0.5 MPa. As shown in Figure 2B, the increased solvent/solid ratio had no obvious effect on polysaccharides yield.…”
Section: Methodsmentioning
confidence: 99%
“…It is also observed in the SWE of other natural product. 58,59 The effect of the solvent/solid ratio on the polysaccharide yield was explored from 15:1 to 55:1 (mL/g) with an extraction temperature of 140 °C, extraction time at 12.5 min, and extraction pressure at 0.5 MPa. As shown in Figure 2B, the increased solvent/solid ratio had no obvious effect on polysaccharides yield.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the whole plants of Hedyotis diffusa Willd. [ 13 ] and Centella asiatica L. [ 14 ] have medicinal values and the leaves, nodes, petioles, and roots of these two herbs were grounded before SBWE. Stems and leaves of ginseng [ 15 ], root of Sophora flavescens Ait.…”
Section: Sample Matrices Extracted By Subcritical Watermentioning
confidence: 99%
“…A comparison of SBWE with traditional extraction technologies (Soxhlet, UAE, and SFE) showed that subcritical water could be a green and efficient substitution for the extraction of sesquiterpene lactones from I. racemose. Xiao et al [ 13 ] developed SBWE for extraction of ursolic acid from Hedyotis diffusa . The RSM model proved to predict the experimental results very well and demonstrated that UA yield was mainly dependent on solvent/solid ratio, followed by particle size and temperature.…”
Section: Compounds Extracted By Subcritical Watermentioning
confidence: 99%
“…Pressure and temperature play the main roles in SWE, as at ambient condition, water is extremely polar, meanwhile, as the conditions vary, the polarity of water could change, depending on its dielectric constant values [1], [15]. In the subcritical water extraction, factors that may affect the research procedure are pressure, temperature, time, solid to solvent ratio, and particle size depending on the plant chosen as raw materials [14], [16]- [19]. There is research conducted in the optimization Salvia Officinalis L. using SWE [20].…”
Section: Green Extraction Of Plant Materialsmentioning
confidence: 99%